Turkey's role in the Western Balkans - Alida Vračić (Stiftung Wissenschaft und Politik (SWP), 2016)
Since the early 1990s, Turkey has come a long way in reasserting itself in the Balkans. The end of the Cold War transformed Turkish foreign policy strategies, which were aimed at securing greater political influence in the Balkans. A lack of coherent policies from the European Union (EU) and the lack of clear goals for the former Yugoslav countries opened up new possibilities for Turkey. Using its so-called soft power, Turkey has created an efficient network of institutions across the region focused on religion, culture, and history. Schools and universities, the Hizmet movement, and Fethullah Gülen's advocates and networks have flourished in the Balkans and nowadays constitute a network of NGOs and religious centers. Using a sentimental interpretation of common history, Turkey has gained considerable influence among Muslim communities, but not much elsewhere. Turkey's public discourse favoring Muslim communities has proved to be a self-imposed limitation, incapacitating Turkey from more meaningful influence in the region as a whole. Moreover, a long-promised economic boost for the region has not been realized. The strong economic growth that Turkey experienced in the early 2000s, which enabled it to make more commitments to the region in the first place, did not help it surpass the economic possibilities offered to the region by the EU. Recent developments in Turkey and its growing authoritarianism make Turkey a less desirable future model to be followed. On the other hand, Turkey's current regime may be appealing to the Western Balkan leaders, who themselves feature more anti-democratic practices. With poor economic prospects and the missing strength of an EU anchor in the Western Balkans, there is a great necessity to synchronize approaches in the Western Balkans. (SWP Research Paper)
Keywords: 320